Fatou, Julia, Montel the great prize of mathematical sciences of 1918, and beyond - Audin, Micháele (Lecture Notes in Mathematics History of mathematics subseries, 2011)
How did Pier Fatou and Gaston Julia create what we now call Complex Dynamics, in the context of the early twentieth century and especially of the First World War? The book is based partly on new, unpublished sources.Who were Pierre Fatou, Gaston Julia, Paul Montel? New biographical information is given on the little known mathematician that was Pierre Fatou. How did the serious WW1 injury of Julia influence mathematical life in France? From the reviews of the French edition: "Audin?s book is indeed filled with marvelous biographical information and analysis, dealing not just with the men mentioned in the book?s title but a large number of other players, too ? . the book under review addresses itself to scholars for whom the history of mathematics has a particular resonance and especially to mathematicians active, or even with merely an interest in, complex dynamics. ? presents it all to the reader in a very appealing form." (Michael Berg, The Mathematical Association of America, October 2009)